Product market competition and the labour market: Evidence from South Africa - Francesco Amodio; Michele Di Maio; Yifan Li; Patrizio Piraino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We study the relationship between product market competition and labour market outcomes in South Africa. We combine firm-level data from tax records with individual-level data from the labour force survey. We estimate markups across sectors, and derive a measure of employment concentration in high-markup sectors across South African district municipalities. We then test whether individual labour market outcomes differ systematically in those district municipalities where employment is more concentrated in high-markup sectors. We find that higher employment concentration in high-markup sectors is associated with higher unemployment and lower likelihood of transitions from unemployment to employment. This is differentially more the case for non-White, lower educated, and young individuals. The relationship remains strong when conditioning on a rich set of individual- and district-level covariates, including employment concentration per se.
Keywords: 330; product market competition; tax data; unemployment